2022
DOI: 10.1007/s00468-022-02341-w
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying effects on tree growth rates of symmetric and asymmetric inter-tree competition in even-aged, monoculture Eucalyptus pilularis forests

Abstract: Key message In even-aged, monoculture eucalypt forest, symmetric inter-tree competition was far more important in determining tree growth rates than asymmetric competition. Tree size principally determined competitive ability at any time. Abstract In even-aged, monoculture forests, individual tree growth rates are much affected by the amount of the resources required for growth (particularly light, water and nutrients) that are available to them from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Restoration thinning promoted the growth of small trees more than large trees, contrary to our expectations. We assumed large river red gums would have a competitive advantage due to the large root systems of mature trees (Bacon et al., 1993; York et al., 2010), the reported suppressive effect of large trees on growth of smaller trees (Opie, 1968), and studies that demonstrated increasing diameter growth rates with tree size in other eucalypts (Bhandari et al., 2021; West, 2022). In our thinning model, slightly increased growth for large trees compared to small trees was only evident within control plots in wetter sites (SQ1) during the wettest year of the study, suggesting that large trees may have a slight competitive advantage in the absence of thinning when water availability is very high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restoration thinning promoted the growth of small trees more than large trees, contrary to our expectations. We assumed large river red gums would have a competitive advantage due to the large root systems of mature trees (Bacon et al., 1993; York et al., 2010), the reported suppressive effect of large trees on growth of smaller trees (Opie, 1968), and studies that demonstrated increasing diameter growth rates with tree size in other eucalypts (Bhandari et al., 2021; West, 2022). In our thinning model, slightly increased growth for large trees compared to small trees was only evident within control plots in wetter sites (SQ1) during the wettest year of the study, suggesting that large trees may have a slight competitive advantage in the absence of thinning when water availability is very high.…”
Section: Discussionmentioning
confidence: 99%
“…Large trees often have structural or physiological advantages that enable them to access a greater share of available resources than small trees and thus grow faster (Coomes & Allen, 2007; Schwinning & Weiner, 1998). This size‐related advantage is described as size‐symmetric competition when growth rates increase in direct proportion to tree size, or as size‐asymmetric competition when large trees grow disproportionately fast compared with small trees (West, 2022). Competition for light in forests is usually size‐asymmetric because the height and spread of large trees allows them to intercept and capture the majority of the resource (Craine & Dybzinski, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The results here suggest that, for the five species considered, it would be practical to develop individual tree growth models that are based on functions that relate maximum growth rates to tree sizes, that is, the functions described in Table 2. The next stage in the development of such models would be to determine the effects on those maxima of changes in site productive capacity and then the effects of inter-tree competition [3,24,44−47]; this has been attempted for E. Pilularis [19,20]. Further work would then be required to extend the model to predict variables of interest to forest management, such as tree height, biomass or stem wood volume; this would often use allometric relationships between those characteristics and stem basal area [33,48−50].…”
Section: Discussionmentioning
confidence: 99%
“…For this study, the method of Bi and Turvey [15] was used, termed here the "class maxima" method. Note that, incorrectly, it has been termed quantile regression [18,19]. This method was considered appropriate for the present work because it uses data that include, unequivocally, the maximum growth rates observed for the tree sizes encountered in the data set.…”
Section: Model Developmentmentioning
confidence: 99%
“…Moreover, crown competition assessed by remote sensing does not fully reflect the competition the tree experiences. Factors such as root competition for water and nutrients, which are important determinants of growth (West, 2023), remain challenging to quantify through photogrammetric measurements. In contrast, competition indices based on field measurements can provide some insight into root competition, as they supply information on all neighboring trees.…”
Section: Remote Sensing Provides Data Complementary To Field Datamentioning
confidence: 99%